UZBEKISTAN’S STRATEGIC APPROACHES OF TO THE SCO ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
The article reveals that Uzbekistan’s strategy towards the Shanghai Cooperation Organization (SCO) always has been based on following principles: (1) ensuring national and regional security in Central Asia (2) preserving independence in foreign policy (3) balancing the interests of major powers in Central Asia (4) preventing hegemony of a single state or a group of states within the SCO (5) using the SCO to implement Uzbekistan's priorities in trade, economy and transport interconnectivity.